ChemInform Abstract: Chromium‐Catalyzed Asymmetric Dearomatization Addition Reactions of Halomethyl Heteroarenes. Issue 33 (27th July 2016) - Tian, Qingshan; Bai, Jing; Chen, Bin; Zhang, Guozhu
Abstract: This protocol provides an efficient access to highly functionalized, optically active benzofurans, benzothiophenes and indanes.